FRACTURE PENIS WITH COMPLETE URETHRAL DISRUPTION DURING INTERCOURSE - Murtaza, Badar; Akmal, Muhammad; Niaz, Waqar Azim; Ahmad, Hussain; Mahmood, Arshad (Journal of Ayub Medical College Abbottabad, 2009)
We present a rare case of fracture penis with complete urethral disruption in a 38 years old male. This resulted in an erect penis during sexual intercourse. He presented with diffuse and tense swelling of the penis along with acute urinary retention and distended urinary bladder. Emergency exploration revealed complete urethral disruption with tears in both corpus cavernosa. Evacuation of haematoma, repair of corpora and primary urethral repair was performed. Post-operative recovery was smooth and the patient developed satisfactory erectile and voiding function. Keywords: Fracture penis, Urethral disruption, Erectile and Voiding function